Layoffs and Productivity at a Bangladeshi Sweater Factory - Robert Akerlof; Anik Ashraf; Rocco Macchiavello; Atonu Rabbani (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Conflicts between management and workers are common and can have significant impacts on productivity. Combining ethnographic, survey and administrative records from a large Bangladeshi sweater factory, we study how workers responded to management's decision to lay off about a quarter of the workers following a period of labor unrest. Our main finding is that the mass layoff resulted in a large and persistent reduction in the productivity of surviving workers. Moreover, it is specifically the firing of peers with whom workers likely had social connections - friends - that matters. Additional evidence on defect rates suggests a deliberate shading of performance by workers in order to punish the factory's management.
Keywords: J50; M50; O12; 330; layoffs; productivity; morale; relational contracts